2006
DOI: 10.1161/01.atv.0000223865.64812.26
|View full text |Cite
|
Sign up to set email alerts
|

Combination of In Vivo Angiopoietin-1 Gene Transfer and Autologous Bone Marrow Cell Implantation for Functional Therapeutic Angiogenesis

Abstract: Objective-Autologous bone marrow mononuclear cell (BM-MNC) implantation into ischemic tissues promotes angiogenesis, but a large amount of marrow aspiration is required, which is a major clinical limitation. Angiopoietin-1 (Ang-1) is requisite for vascular maturation during angiogenesis. We examined the impacts of combinatorial Ang-1 gene transfer and low-dose autologous BM-MNC implantation on therapeutic angiogenesis in a rabbit model of hind limb ischemia. Methods and Results-Rabbits were divided into 4 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 56 publications
(69 reference statements)
3
27
0
Order By: Relevance
“…This was evidenced by an absence of any signs of neoplastic angiogenesis in the necropsy material. Similar results have been observed by other researchers [11,12,14,15]. However, to evaluate the safety of the Ang-1 plasmid administration, longer observation of a larger group of animals is needed.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This was evidenced by an absence of any signs of neoplastic angiogenesis in the necropsy material. Similar results have been observed by other researchers [11,12,14,15]. However, to evaluate the safety of the Ang-1 plasmid administration, longer observation of a larger group of animals is needed.…”
Section: Discussionsupporting
confidence: 88%
“…VEGF and Ang-1 may also activate the expression of proangiogenic genes. Moreover, Ang-1 is also known to stabilize newly formed vessels [14][15][16][17].…”
mentioning
confidence: 99%
“…In this view, administration of a plasmid encoding Ang-1 with autologous bone marrow cell injection enhances neovascularization in a rabbit hindlimb ischemia model compared with BM-MNC implantation alone. 35 These results suggest that the increase efficiency of cotherapy results from the release of Ang-1 by SMPCs, leading to the activation of Tie2 at the EPC surface and subsequently to the activation of EPC-related functions. Nevertheless, it is likely that SMPCs have other effect than just a secretion of Ang-1.…”
Section: Discussionmentioning
confidence: 77%
“…Recent studies have shown that a combination of stem cell transplantation and angiogenic or antiapoptotic factors or genes synergistically enhanced neovascularization in ischemic tissues compared with each therapy alone. 27,28 Coadministration of several growth factors enhanced ESC engraftment and hostspecific differentiation in hearts with myocardial infarction. 29 Thus, combination therapy could be used to enhance the angiogenic efficacy of hESC-EC transplantation.…”
Section: Cho Et Al Hesc-derived Functional Endothelial-like Cells 2415mentioning
confidence: 99%